How Much of the Earth's Surface is Underlain by Permafrost? - Obu, J. (Journal of geophysical research. Earth surface, 2021)
More than 80% of studies reporting the area on Earth underlain by permafrost refer to the extent of the permafrost region, which accounts for around 21 million km2 (22% of the Northern Hemisphere's exposed land surface). Since each permafrost zone (continuous, discontinuous, sporadic, and isolated, which combined represent the permafrost region) is not entirely underlain by permafrost, the actual area underlain by permafrost (permafrost area) accounts for approximately 14 million km2 (15% of the exposed land surface area in the Northern Hemisphere). Such overstatements create a general impression that there is 6 million km2 more permafrost than currently estimated. I highlight the known differences between the terms permafrost region and permafrost area, along with explaining the possible reasons leading to these overstatements. Recent studies estimating permafrost area extent are summarized to provide a baseline for the geoscientific community and general public about the actual area underlain by permafrost for different parts of the globe. Plain Language Summary It is frequently reported that permafrost underlies a quarter of the Northern Hemisphere. This estimate is based on the total area of all permafrost zones (continuous, discontinuous, sporadic, and isolated patches). Since these permafrost zones are not entirely underlain by permafrost, the proportion of permafrost underlying the Northern Hemisphere is substantially smaller. Permafrost thus underlies approximately 15% of the Northern Hemisphere, which is about three times the area of Greenland less than the commonly reported estimate. This commentary highlights possible reasons that caused this too large value to be frequently reported and provides permafrost area estimates for different parts of the globe. Key Points The spatial extent of permafrost is frequently overstated within the literature This overstatement is due to confusion between the terms “permafrost region” and “permafrost area” Current estimates show that approximately 15% of the Northern Hemisphere is underlain by permafrost